New directions in island biogeography - Santos, Ana M.C.; Field, Richard; Ricklefs, Robert E. (Wiley, 2016)
Aim: Much of our current understanding of ecological and evolutionary processes comes from island research. With the increasing availability of data on distributions and phylogenetic relationships and new analytical approaches to understanding the processes that shape species distributions and interactions, a re-evaluation of this ever-interesting topic is timely.